Prasugrel Versus Clopidogrel: A Comparative Examination of Local Bleeding After Dental Extraction in Patients Receiving Dual Antiplatelet Therapy - Dézsi, Balázs Bence; Koritsánszky, László; Braunitzer, Gábor; Hangyási, Dávid Botond; Dézsi, Csaba András (Journal of oral and maxillofacial surgery, 2015)
To study the effects of various parameters on local hemostasis after dental extraction in patients receiving different combinations of medications who had previously confirmed effective dual inhibition of platelet aggregation. A total of 129 patients were enrolled. They underwent acute or planned percutaneous coronary intervention and their stomatological examination disclosed teeth that could have acted as foci and thus had to be removed. All patients took acetylsalicylic acid 100 mg and clopidogrel or prasugrel. Lidocaine with or without epinephrine was used for local anesthesia, and a gauze swab or suture was applied to help hemostasis. Bleeding time was significantly longer by an average of 10 minutes (+21%) in patients taking prasugrel (P < .05) compared with those taking clopidogrel. Use of a suture resulted in a significantly shorter bleeding time after anesthesia with or without epinephrine (P < .05). A considerably longer bleeding time was observed when anesthesia with no epinephrine was combined with gauze. In smokers, the bleeding time was shorter by 15% on average. This study is the first to analyze differences in bleeding times between clopidogrel and prasugrel treatments during dental extraction. In general, prasugrel is associated with a considerably longer bleeding time; nevertheless, dental extraction can be performed safely with either combination.